ANALISIS WACANA VAN DIJK TERHADAP ANIMASI RELIGI “NEGARA ISLAMI” (KARYA CISFORM UIN SUNAN KALIJAGA & PPIM UIN JAKARTA) - Rif’atul Khoiriah Malik (Ilmu Komunikasi UIN Alauddin Makassar, 2019)
The concept of khilafah which became a debate among the public triggered several conflicts in Indonesia. This concept does not escape the system of government of the country. If you look back at the history of Islam where the Prophet Muhammad held the